MITOLOGI TIONGHOA DALAM ANTOLOGI PUISI KONDE PENYAIR HAN DAN BENIH KAYU DEWA DAPUR KARYA HANNA FRANSISCA - Shella Angellia Rimang; Chairil Effendy; Sesilia Seli (Universitas Tanjungpura, 2019)
AbstractPoetry’s literature is closely related to the daily’s life of society and cultural elements of society, especially the cultural elements of the author. The anthology of poets Konde Penyair Han and Benih Kayu Dewa Dapur was chosen as the research object because the poets has the basic of Chinese’s culture, that converges becomes Chinese’s mythology. The method in these research is descriptive qualitative terms. The approach that used is mythopoic. The data source in these research is the anthology of poets Konde Penyair Han and Benih Kayu Dewa Dapur by Hanna Fransisca, while the data is the form, function, and the meaning of the myths contained into the form of words, lines, and verses of the poetry. Based on the results of data analysis, concluded that (1) of the eight poems analyzed, the mythical form of the gods (supernatural creatures) is the most dominated form, (2) of the eight poems analyzed, only the poems “Cap Go Meh” and “Doa Sajak Vihara” which has no function to ensure the efficiency of the rite and provides the practical rules to guide peoples, and (3) the meaning of the myth is researcher's interpretation against the myths which contained in those poems based on four perspectives about those means, specifically for pengertian (sense), perasaan (feeling), nada (tone), and niat (intention).Keywords: mythology, mythopoic, poetryAbstractPoetry’s literature is closely related to the daily’s life of society and cultural elements of society, especially the cultural elements of the author. The anthology of poets Konde Penyair Han and Benih Kayu Dewa Dapur was chosen as the research object because the poets has the basic of Chinese’s culture, that converges becomes Chinese’s mythology. The method in these research is descriptive qualitative terms. The approach that used is mythopoic. The data source in these research is the anthology of poets Konde Penyair Han and Benih Kayu Dewa Dapur by Hanna Fransisca, while the data is the form, function, and the meaning of the myths contained into the form of words, lines, and verses of the poetry. Based on the results of data analysis, concluded that (1) of the eight poems analyzed, the mythical form of the gods (supernatural creatures) is the most dominated form, (2) of the eight poems analyzed, only the poems “Cap Go Meh” and “Doa Sajak Vihara” which has no function to ensure the efficiency of the rite and provides the practical rules to guide peoples, and (3) the meaning of the myth is researcher's interpretation against the myths which contained in those poems based on four perspectives about those means, specifically for pengertian (sense), perasaan (feeling), nada (tone), and niat (intention). Keywords: mythology, mythopoic, poetry